Effect of Different Levels of Nitrogen and Phosphorous Fertilizers on Productivity of Potato (Spunta) (Solanum tuberosum.L) and Some Soil Properties in Damascus Countryside (Damascus University Journal of agriculture sciences, 2024)
The research was conducted at the Agricultural Scientific Research Center, at Al-Nashabiya Research Station in Damascus Countryside, during the summer season (2021), with the aim to study the effect of different levels of nitrogen and phosphorous fertilizers of the approved fertilizer recommendation, on crop productivity.Potato (Spunta variety) compared to the control (without fertilization) With the following values (50%)  less the current fertilizer recommeudation (130.5.kg.ha-1nitrogen 65.kg.ha-1phosphorous), (75%)less the current fertilizer recommeudation (195.75kg.ha-1nitrogen ,97.5kg.ha-1 phosphorous), (100%) according to the current fertilizer recommeudation (261 kg.ha-1nitrogen, 130kg.ha-1 phosphorous), (125%) more than the current fertilizer recommeudation(326.25kg.ha-1nitrogen,162kg.ha-1phosphorous). The experiment was laid out according to randomized complete block design (R.C.B.D) with five fertilizer treatments and three replicationss. The characteristics of NPK fertility soils were studied, in addition to the characteristics of plants in terms of the ratios of these elements in leaves and tubers and the productivity. Among the qualitative characteristics studied are the percentage of starch and the percentage of protein. It was noted that the increase in the rate of adding nitrogen and phosphorous fertilizers resulted in an increase in the soil content of available nitrogen and phosphorous elements, as well as an increase in the nitrogen and phosphorous content of potato leaves and tubers. It was also noted that there were no significant differences between the two fertilizer recommendations 75% and 100% in the studied indicators. Where the amount of nitrogen and phosphorous available in the soil for fertilizer treatment reached 125%, the highest value was (12.10) mg.kg-1 nitrogen (8.77) mg.kg-1 phosphorous. As for the control, the lowest value was recorded (8.70) mg.kg-1 nitrogen (4.62) mg.kg-1 phosphorous, as well as for nitrogen and phosphorous in the leaves. The highest value was recorded for the fertilizer treatment: 125% (1.15%) nitrogen, (0.35%) phosphorous, and the lowest value was when treating the control (0.84%) nitrogen (0.20%)phosphorous, as Increasing the rate of adding mineral fertilizers, both nitrogen and phosphorous, improved the potato growth rate, and increased the average yield and quality of potato tubers compared to the control. Where the lowest amount of production was recorded in the control treatment, which amounted to (18.91) tons/ha, with significant differences with the rest of the treatments. While the treatment was 125%, the highest productivity amounted to (35.37) tons / ha, and the apparent differences between the two fertilizer treatments were 75% and 100%.
Keywords: Nitrogen fertilizer; phosphorous fertilizer; soil properties; quantitative characteristics; qualitative characteristics; potatoes